(untitled) (PERcursos Linguísticos, 2020)
this paper seeks to highlight the open controversies and dialogical relations raised by the discourse presented in na oficial statement in national chain by the President of the Republic Jair Bolsonaro on the night of march 24,2020. For this endeavor, we resort to the theoretical and methodological constructs of Dialogical Discourse Analysis, having as instruments of analysis the concepts of utterance, dialogical relations and open controversy. In organizational terms, we use as basis the pronouncement made available on the oficial page of the federal government. In our final remarks, we observed dissonante dialogical relations to what was recommended by the World Health Organization, as well as by Brazilian health authorities, governos and mayors, going against everything that science recommended, characterizing a discourse of resistance to what was proven by science and experience of countries that went through the pandemic before Brazil.